DOES THE INDEPENDENT BOARD OF COMMISSIONERS MODERATE THE DETERMINANTS INFLUENCING ACCOUNTING CONSERVATISM? - Sulina, Ketrine; Lusmeida, Herlina (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2026)
Conflicting findings about what drives accounting conservatism raise doubts about the reliability of financial reports. This study examines how financial distress, capital intensity, and profitability affect accounting conservatism, with independent commissioners as a moderating variable. Using purposive sampling, it analyzes 104 manufacturing firms in the industrials and consumer staples sectors listed on the Indonesia Stock Exchange from 2019 to 2023. Panel data estimation is applied. The results show that financial distress has no significant effect on accounting conservatism, while capital intensity and profitability have significant positive effects. Independent commissioners do not moderate the effects of financial distress and profitability on accounting conservatism. Although they significantly moderate the relationship between capital intensity and accounting conservatism, they do not strengthen its positive impact. These findings offer useful insights for investors and regulators in evaluating earnings quality and improving transparency in financial reporting.